Nutraceuticals in Viral Infections: A Comprehensive Review on the Natural Occurrence and Therapeutic Potential of Resveratrol, Quercetin, and N-Acetyl Cysteine - Vakte, Sanket Rajendra; Nehete, Jitendra Yadav; Sonawane, Chinmay Pradip; Pawar, Vaibhav Kailas (Asian Journal of Biological and Life Sciences, 2025)
In recent years, there has been a growing interest in using nutraceutical supplements as adjuvants to treat viral infections. Nutraceuticals are food-derived, non-pharmaceutical substances that have demonstrated antiviral and other possible health advantages. The purpose of this review is to provide an overview of available data regarding the safety and efficacy of several nutraceutical supplements in the management of viral infections. Electronic databases and the reference lists of pertinent publications were used to perform a thorough search of the literature. The most widely used nutraceutical supplements for the treatment of viral infections were the subject of the search, which included both human and animal research. The review's findings imply that certain nutraceutical supplements, including N-acetyl cysteine, quercetin, and resveratrol, may be useful adjuvants in treatment of viral infections. The natural sources, modes of action, and therapeutic potential of these nutraceuticals in viral infections are highlighted in this review. Their effectiveness is supported by preclinical and clinical research, although more work is required to determine standardised dosage, bioavailability, and synergistic effects with traditional antiviral treatments. A viable method of treating viral infections may be provided by including these nutraceuticals into therapeutic and preventative plans.
Keywords: Antiviral treatments; N-Acetyl Cysteine; Nutraceutical; Quercetin; Resveratrol